The Wayward Witch & the Feelings Monster - Rippin, Sally (Hardie Grant Egmont, 2017)
In a world where witches can never be friends with monsters, Polly and Buster have managed to keep their friendship a secret. Until one day, when everything changes . .
Keywords: Australian; Witches / Juvenile fiction; Monsters / Juvenile fiction; Friendship / Juvenile fiction; Friendship; Monsters; Witches; Fiction; Juvenile works; Kinderbuch